Potential Carbon Stock in Revegetation Stand of Post-Mining Land at PT Jorong Barutama Greston, South Kalimantan POTENSI SIMPANAN KARBON PADA TEGAKAN REVEGETASI LAHAN PASCA TAMBANG DI PT JORONG BARUTAMA GRESTON, KALIMANTAN SELATAN - Iwan Hilwan; Ade Siti Nurjannah (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
Mining activities can generate the lost of vegetation that cause absorption of CO2 decrease. Reclamation and revegetation activities were expected could increase the absorption of CO2. The aims of this research are to presume and to compare carbon stock in revegetation stand of post-mining land in 2008, 2009, and 2010 cultivation at PT Jorong Barutama Greston. The estimation of carbon stock in Acacia mangium and Paraserianthes falcataria were conducted with allometric model while destructive sampling was used for litter and understorey. Total carbon stock of revegetation stand in 2008, 2009, and 2010 were 41.09, 27.43, and 22.90 ton/ha. The analysis value of vegetation showed that total species of understorey in 2008, 2009, and 2010 were 20, 19, and 26 specieses. The value of Pearson correlation test showed that understorey diversity state had not a significant effect for its carbon stock.Keywords: Acacia mangium, carbon stock, Paraserianthes falcataria, revegetation stand